Hypertrophic osteoarthropathy: classification, diagnostic features, and treatment options. (2nd August 2016) - Galuppi, Elisa; Bortoluzzi, Alessandra; Govoni, Marcello; Trotta, Francesco
ABSTRACT: Introduction : Hypertrophic osteoarthropathy (HOA) is an orphan disease characterized by digital clubbing, periostitis of tubular bones and arthralgia/arthritis. The disease may be classified as primary or secondary. Pulmonary and other intra-thoracic diseases are the cause of more than 90% of the secondary forms. Areas covered : The diagnosis is generally based on the presence of a triad of symptoms including digital clubbing, periostitis of the distal end of the tubular bones and painful swelling of the limbs, associated with bilateral and symmetrical arthritis in the large joints. Radiographic evaluation is the assessment reference for the diagnosis. Vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF) seem to be the key mediators in the pathogenesis of this disorder. Treatment and prognosis depend on the HOA underlying cause. In some cases, treatment of associated malignancy can solve or improve clubbing. Bisphosphonates may have a role for the symptomatic treatment of HOA. Expert opinion : In clinical practice primary HOA is rare while secondary form is relatively frequent and may mimic other rheumatologic conditions. Notably HOA should be considered in the differential diagnosis of painful arthritis with periosteal bone involvement and if clubbing or periostitis become evident in a previously healthy individual a comprehensive search for an underlying illness should be undertaken.